Efeitos da violência de gênero nos games: análise das manifestações comunicacionais expressas no twitter na campanha #soumulhersougamer - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present work discussed the existing gender-based violence in games and analyzed the effects understood from the communicational manifestations of women gamers about the situations experienced in the digital games environment and in the gamer community. Gender-based violence is an expression of misogyny in our society and affects women because they are women. Furthermore, it takes place both in the material and digital worlds. In 2019, the #SouMulherSouGamer campaign was created with the aim of guaranteeing a space for women gamers to speak out about the gender-based violence suffered by them in games. In this work, we found that the #SouMulherSouGamer (2019) campaign is one of the examples of hashtivism and cyberactivism practices today. This dissertation brings as a theoretical basis the issues that involve the social construction of gender presented and discussed by several authors (BEAUVOIR, 1967, 1970; STOLLER, 1968; OAKLEY, 1972; DELPHY, 2001; GARCIA, 2015 and FEDERICI, 2017), the violence against women (SEGATO, 2016) as well as violence expressed in the digital environment (SILVA ET AL, 2011 and MEIRA, 2021), the communicational manifestations existing in cyberspace (MARTINO, L.M.S. 2018; RECUERO, 2009, 2012, 2019; CARVALHO , 2010; BARICHELLO; CARVALHO, 2012), cyberactivism and the practice of social listening (MALINI, 2013; MARTINS, 2014; RESENDE; FREITAS; OLIVEIRA, 2015; YANG, 2016; KOTLER; KARTAJAYA; SETIAWAN, 2017) in addition to a current perspective of the games industry (SUPER DATA, 2019, 2020; NEW ZOO, 2021; PGB, 2022) and the theoretical considerations about gender inequality and gender-based violence in games (KURTZ, 2019). We performed content analysis (BARDIN, 1977) and found that the effects produced by the communicational manifestations of women gamers in the #SouMulherSouGamer (2019) campaign can be understood through different perspectives such as the silent and invisible presence of women in the gaming environment, in addition to the need for game developers to use social listening in hashtivism campaigns in order to identify the problems experienced by women gamers and pay attention to the necessary changes to make games a more equal environment.
Keywords: Violência; Identidade de gênero; Comunicação; Redes sociais on-line; Jogos; Twitter (Rede social on-line); Violence; Gender identity; CNPQ::CIENCIAS SOCIAIS APLICADAS